A qualitative analysis of immigrant population health practices in the Girona Healthcare Region - Vall-llosera L; Saurina C; Saez M (BMC, 2010)
Abstract Background The research we present here forms part of a two-phase project - one quantitative and the other qualitative - assessing the use of primary health care services. This paper presents the qualitative phase of said research, which is aimed at ascertaining the needs, beliefs, barriers to access and health practices of the immigrant population in comparison with the native population, as well as the perceptions of healthcare professionals. Moroccan and sub-Saharan were the immigrants to who the qualitative phase was specifically addressed. The aims of this paper are as follows: to analyse any possible implications of family organisation in the health practices of the immigrant population; to ascertain social practices relating to illness; to understand the significances of sexual and reproductive health practices; and to ascertain the ideas and perceptions of immigrants, local people and professionals regarding health and the health system. Methods Qualitative research based on discursive analysis. Data gathering techniques consisted of discussion groups with health system users and semi-structured individual interviews with healthcare professionals. The sample was taken from the Basic Healthcare Areas of Salt and Banyoles (belonging to the Girona Healthcare Region), the discussion groups being comprised of (a) 6 immigrant Moroccan women, (b) 7 immigrant sub-Saharan African women and (c) 6 immigrant and native population men (2 native men, 2 Moroccan men and 2 sub-Saharan men); and the semi-structured interviews being conducted with the following healthcare professionals: (a) 3 gynaecologists, (b) 3 nurses and 1 administrative staff. Results Use of the healthcare system is linked to the perception of not being well, knowledge of the healthcare system, length of time resident in Spain and interiorization of traditional Western medicine as a cure mechanism. The divergences found among the groups of immigrants, local people and healthcare professionals with regard to healthcare education, use of the healthcare service, sexual and reproductive healthcare and reticence with regard to being attended by healthcare personnel of the opposite sex demonstrate a need to work with the immigrant population as a heterogeneous group. Conclusions The results we have obtained support the idea that feeling unwell is a psycho-social process, as it takes place within a specific socio-cultural situation and spans a range of beliefs, perceptions and ideas regarding symptomology and how to treat it.